Deza and Its Moriscos : Religion and Community in Early Modern Spain - O'Banion, Patrick J., 1975- (Book collections on Project MUSE., 2020)
"Deza and Its Moriscos refocuses historiographical debates about the so-called Morisco problem, a defining crisis for early modern Spain. Drawing deeply upon a diverse collection of archival material as well as early printed works, this study illuminates internal conflicts, external pressures brought to bear by the Inquisition, episcopacy, and crown, as well as the possibilities and limitations of negotiated communal life at the dawn of modernity"--